The Limits of Consciousness A Conversation with Martin Monti. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Martin Monti, Associate Professor in Psychology and Neurosurgery, Brain Injury Research Centre, UCLA. This wide-ranging conversation examines Martin Monti's innovative work with patients who are in a vegetative state or minimally conscious state which has led to some surprising results which might well prove to be integral to our development of a deeper understanding of consciousness.This carefully-edited book includes an introduction, The Collective Unconscious, and questions for discussion at the end of each chap.